Pengaruh Kompetensi, Pengalaman dan Pelatihan terhadap Prestasi Pegawai Pada Kantor Kecamatan Klungkung - Utami, Dewa Ayu Mirah; Kawiana, I Gede Putu; Kusyana, Dewa Nyoman Benni (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This rsesearch was condufcted at the Klungkung subjdistrict offiice located in Klungkung District, Klungkung Regeincy. The populatioun in this studying were all employees of the Klungkung District Office, totaling 32 people. This research uses census technique method. Data collection was carriesd out by intetrviews, questionnaires, and literature. A Likert scale with five response options is the measuring scale that is employed. The vaildity and reliability of the instrument were tested in order to conduct the test. Multiple linear regression analysis is done using SPSS software. According to the results of the determination test, 73.4 percent of an work's performance is influenced by their competence, work experience, and job training. The findings of the partial significance test demonstrate that job training, work experience, and competency all have positive and significant effects on work performance. Suggestions given include socializing SOPs, maintaining the composition of new and senior employees, and providing training according to employee positions and titles.